Ethnological, Teleological and Axiological Components of the Traditional Upbringing in the Early 20th Century in Bosnia and Herzegovina - Tomić, Draženko; Legac, Vladimir (Acta humanitarica academiae Saulensis, 2019)
This paper looks at and compares two books. The first is entitled “The Life and Practices of Croats of Catholic Faith in Bosnia and Herzegovina” (Sarajevo, 1908) and was written by Nikola Buconjić (1865–1947), a poet, prose writer and ethnographer. The title of the second one is “Muslim Life and Practices in Bosnia and Herzegovina” (Sarajevo, 1907, 2nd ed.). It was written by Antuna Hangija (1866–1909), an ethnographer and folklorist. Both writers worked as teachers. The books served to look at the foundations, methodologies, teleology and axiology of the process of raising children at the beginning of the 20th century in one part of the Bosnian-Herzegovinian population. It has been noted that the process of raising children is based on respect for authority and family hierarchy focusing on the child at the end of that process. The authority, on the other hand, builds its foundation on the right to have access to material goods and is further reinforced by tradition, social system and religion. Implementation (methodology) of the educational process is marked by minimal technical, educational and medical conditions, with a high percentage of child mortality. According to the traditional pattern of education, it was considered that it was necessary to allow an immature individual to adopt a form of socially acceptable behaviour based on respect for authority (teleology) according to the principle: the child is allowed – the child is forbidden. The relevant authorities are parents, followed by teachers or the state, and the church. With the development of the means of production and the raising of the level of literacy and schooling, the conditions can be reached for the child to be raised as an independent and self-aware individual and a responsible member of society. The results of the research study conducted for the purpose of this article have shown low familiarity of today’s young generation with the popular beliefs from Buconjić’s and Hangi’s books.
Keywords: education; authority; educational teleology and axiology